PRIVACY PROTECTION AND THE USE OF FACIAL RECOGNITION TECHNOLOGY IN PUBLIC SURVEILLANCE: LEGAL PERSPECTIVES AND POLICY IMPLEMENTATION IN THE DIGITAL ERA - Yonatan Kornelius Simanjuntak1 Yonatan Kornelius Simanjuntak1 Yonatan Kornelius Simanjuntak1; Daffa Triakhsan Putra; Gragela L. Panjaitan; Christopher Geraldo Siregar; Natasya Sabatini Putri Pangaribuan5 Natasya Sabatini Putri Pangaribuan5 Natasya Sabatini Putri Panga (Problematika Hukum, 2023)
The rapid development of facial recognition technology through artificial intelligence has raised various issues related to privacy and human rights. This is because this technology opens up the potential for abuse and violations related to this matter. In Indonesia, there are several regulations and laws that apply regarding information and technology and data privacy. Such as Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law), Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law), Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, Law Number24 of 2013 concerning Population Administration (Population Administration Law), Law Number 27 of 2022. Of course, there will continue to be challenges in dealing with the impact of facial recognition technology on society and the government. Therefore, it is very important for the public to learn about technology and start being tech-savvy, and it is very important for the government to make specific regulations on facial recognition technology. In addition, agile governance structures are also needed to adapt to technological advancements, such as oversight mechanisms, audits, and public consultations. These measures are essential to manage risks andprotect privacy and individual rights in the digital age.Keywords: Artificial Technology; Facial Recognition Technology; Human Rights; Information and Technology Law